Tinjauan Yuridis Perlindungan Hukum Bagi Konsumen Pinjaman Online di Indonesia - Anis; Zuhrah; Didik Irawansah (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine consumer protection for users of fintech services (Peero-Peer Lending) in the perspective of consumer protection law in Indonesia and to find out efforts to resolve disputes against JULO application Fintech Peer To Peer Lending services. This research uses normative juridical methods with statutory and conceptual approaches. As a literature research, the main focus is on analyzing primary legal materials such as Law No. 8 of 1999 concerning Consumer Protection, Law No. 11 of 2008 concerning ITE, as well as various OJK regulations including POJK No. 10/POJK.05/2022. A statutory approach is applied to comprehensively review regulations relevant to online loan consumer protection, while a conceptual approach is used to analyze theories of consumer protection, principles of justice, and legal certainty. This research aims to provide an in-depth understanding of the legal framework governing consumer protection in online lending services as well as its implementation in practice. This research reveals that although FinTech P2P Lending consumer protection in Indonesia has a strong legal foundation through the Consumer Protection Law and POJK No. 77/POJK.01/2016, its implementation still faces challenges in the form of regulatory gaps with practices in the field. The study on the JULO platform shows that 78% of complaints are resolved through internal mechanisms, while adjudication is an effective solution with an 85% satisfaction rate and faster resolution time (14 working days). The findings identified three main issues: inconsistency in the application of rules, low consumer legal literacy (42%), and the complexity of cross-jurisdictional disputes. The research recommends strengthening OJK's technology-based supervision, improving consumer education, and optimizing adjudication, emphasizing the importance of collaboration between regulators, businesses, and communities to create an equitable and sustainable P2P Lending ecosystem.